SCIENCE, TECHNOLOGY AND THE SAFETY OF WORKERS (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2023)
This article aims to analyze brazilian legislation and the important role of science and technologies in the implementation of measures aimed at the well-being and safety of workers. It is taken as a starting point that in the corporate environment, managers are increasingly aware of the relevance of quality of life and the need to develop and apply better conditions for the well-being of workers. All those who have invested have already started to reap the results of this interaction between company and worker, proving that the professional produces more and better when he feels happy and motivated. The innovation process is complex, nonlinear, uncertain, demand for interaction between professionals, institutions and managers and is dependent on the socio-economic context. Thus, due to the great advances of technology associated with the improvement of education, the demands in relation to working conditions have changed, that is, what was previously tolerated, in certain situations today it has become unacceptable. Investments in the area of work safety are compensated due to the productivity gains of employees, improving working conditions and safety for employees, being converted into a greater competitiveness of the company in the market.